Why we don’t say what we mean: A study of verbal indirection in communication - Ali, Jamaliah Mohd. (Journal of Modern Languages, 2017)
This paper deals with the study of language as a tool of interaction. It looks at various kinds of meanings which can be conveyed in language; meanings which involve the interaction between the speaker and the hearer. In this paper. I would like to demonstrate that in everyday interaction, people make linguistic choices in encoding and decoding messages in accordance with systems that are internally consistent for each individual and may differ from one individual to the next and that these differences can explain misunderstandings that may occur. This paper also aims to explore the strategies through which indirectness finds expression in conversations, the role it plays in "face-work" (Goffman. 1959) and in polite behaviour (Brown and Levinson. 1978) and why interactants abstain from directness. The above discussion will also examine the cultural influence in the verbal indirection of the Malays.